Regional governance and European Structural and Investment Funds at the frontiers of Bavaria - Sabine Weizenegger; Markus Lemberger (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
This article examines the implementation and effectiveness of the European structural and investment funds with regard to regional governance. The study uses the example of development processes in two border regions in Bavaria, the district of Cham on the Bavarian-Czech border and the district of Oberallgäu on the Bavarian-Austrian border. The focus is on LEADER (the EU programme for rural areas) and INTERREG/ ETC (the EU programme for territorial cooperation). A case study seeks to identify indications and structural patterns of operational implementation. Although both instruments show positive effects overall along the Bavarian border regions, there are also clear indications of unintended errors in governance, leading to a loss of efficiency. In particular, non-continuous long-term funding conditions and objectives pose problems. However, within these regions creative adaptations of project ideas to the relevant topics and target strategies can be identified. Therefore, the authors call for more confidence in endogenous potentials on the regional level, including in relation to cross-border cooperation. In order to avoid frictional losses and to increase the effectiveness of the instruments, a stringent orientation towards strategies should be further pursued.
urn:nbn:de:0156-41580755; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Regional governance; European structural and investment funds; Allgäu; Cham; border regions; regional development; LEADER; INTERREG